Repair of a giant omphalocele defect using tissue expansion and Gore-Tex mesh following loss of durable repair with Alloderm: A case report - Evan Fang; Karen A. Bailey; Matthew Choi (Elsevier, 2024)
Introduction: Alloderm is commonly used in abdominal wall reconstruction, however its integrity can fail in the long term. We describe the repair of a giant omphalocele defect in a seven-year-old female who previously underwent an initial closure at birth using Alloderm, which stretched over time. Case presentation: A female infant underwent abdominal wall repair using Alloderm mesh to for a ruptured giant omphalocele in the context of local infection that prevented tissue expansion. While providing good initial coverage, the Alloderm stretched over time, resulting in a large persistent abdominal wall defect. The patient underwent attempted reduction using an abdominal binder with limited success. At 6.5 years of age, the patient underwent bilateral flank tissue expander and scar tissue mobilization to prepare for skin advancement. At 7 years of age, the patient underwent definitive abdominal wall reconstruction using Gore-Tex DualMesh with removal of the tissue expanders. Postoperative management included continued use of an abdominal binder and vacuum-assisted closure. At 4 years and 4 months after the reconstruction, the abdominal wall remains stable with good respiratory, alimentary, and digestive function. The patient continues to grow well and tolerate all physical activities, with no recurrent herniation. Conclusion: The tendency for Alloderm to stretch over time limits its utility for abdominal wall repair in giant omphaloceles. In our case, it did serve as a successful bridge to definitive closure in the context of active infection at birth.